Exploraciones sobre las diversidades desde la literatura infantil: un primer acercamiento (Altre Modernità, 2019)
Literature is a fundamental piece to defend ourselves from everyday life and violence in which all people are immersed. Sometimes we forget that this reality does not treat children with kindness, but as their peers showing the harshness that exists in society and proving that at their young age, children live violations of their human rights. This makes us reflect on the role of children's literature in this society and how it is a fundamental tool for cultural change, which, in conjunction with international laws and treaties, enhance the efforts that exist already so that children are not victims of violence. Children's literature breaks with adult centrism, to become a space that values ​​human life, that understands the complexity of our constitution as a plural society and the diversities in which all people are immersed.